Effectiveness of the use of organic waste as fertilizer and physical scarification of seeds on growth of seeds nila plants (Indigofera sp.) - Roeswitawati, Dyah; Huda, M; Indratmi, D; Mel, Maizirwan (IOP Publishing, 2019)
Tilapia (Indigofera sp.) is used as animal feed because it has a crude protein content of 28.98 % and crude fiber content is 8.49 %, so it is considered as an energy source rich in nutrients. Tilapia plants are plants that are adaptable in a variety of diverse environmental conditions, such as acid soils and long dry climates. Utilization of tilapia as animal feed is very limited because farmers and breeders are reluctant to cultivate it. The limitation of providers of tilapia seedlings is one of the causes of the small number of tilapia cultivated by farmers and breeder so that the need for forage feeds of ruminants to meet protein needs is still lacking. During this time for the needs of ruminants, breeders only depend on natural grass and crop residues. The process of seed germination and tilapia growth after the germination period can be increased by scarifying seeds and using organic fertilizers. The study aimed to determine the effect of using organic waste and the length of physical seed scarification on the growth of tilapia seedlings. The study used factorial experiments (two factors) arranged randomly in groups. The first factor is the type of waste: M0 (without waste); M1 (banana [Musa sp.] hump waste); M2 (papaya fruit [Carica papaya L.] waste). The second factor is the duration of physical scarification (70 °C hot water immersion): S0 (without soaking); S1 (soaked for 7.5 min); S2 (soaked for 15 min). The results showed that there was an interaction between the types of organic waste and the length of seed scarification for tilapia growth. The best treatment is banana hump waste with physical scarification of 15 min of seed.